The Story of the Holocaust - Clive Lawton (London Franklin Watts, 1999)
The Story of the Holocaust describes how over 10 million people - mainly Jews, but also gypsies, Jehovah"s Witnesses, homosexuals, trade unionists and socialists - came to be murdered by the Nazi regime.'
Keywords: Eras Of History - Historical Events -- Eras Of History - Historical Events